Gender diversity in Corporate Governance: A study of the largest listed companies in Bombay Stock Exchange - Walanju, Kishore (2012)
High profile scandals in US and other emerging economies as well as the recent global financial crisis have enhanced global interest on the topic of corporate governance. The scandals have drawn attention to the functioning and weakness of corporate boards and companies are trying to improve their corporate governance. Among the areas targeted for improvement by companies include gender diversity on corporate boards. Gender diversity is one of the measures by which companies are using to achieve their targets in areas such as transparency, increasing shareholders value, corporate board performance and representing stakeholders. Gender diversity on corporate boards is considered a social issue as well as value driver in company strategy. India is an emerging economy in the world and public listed companies are major contributors in development. Therefore effective functioning of corporate boards is important in enhancing better corporate governance in India. The objective of this study was to examine gender diversity on corporate boards of Indian companies. This includes representation of woman on corporate boards of Indian companies. Besides, the study examined barriers and enablers of women representation on corporate boards of India at the same time it investigated the impact of UNGC code in inclusion of women on corporate boards in India. The finding of study reveals that the level of women representation on corporate boards in India is very low and far from adequate. Besides, the study established no significant difference in women representation on corporate boards of BSE 100 and UNGC signatory companies. This study concludes that UNGC as an enabler has not fully acted as a catalyst for women inclusion on corporate boards of India, suggesting that the more needs to be done by the UNGC network in India. Moreover, the study examined barriers and found that Tokenism in top management and Old boy networks are the most prominent barriers to women to women representation on corporate boards. The findings show that competency serves as an effective enabler in corporate practices. Besides, enablers such as Ministry of Corporate affairs, Ministry of Women and Child development, National commission for women and the Securities and Exchange Boards of India (SEBI) are silent to implement the principle of gender equality as enshrined in constitution of India. However, existence of the provision of gender equality in the constitution provides legal foundation for special laws to enhance women representation on corporate boards in India.